Clinical significance of spleen stiffness in patients with acute decompensated heart failure. (13th September 2020) - Saito, Yuki; Matsumoto, Naoki; Aizawa, Yoshihiro; Fukamachi, Daisuke; Kitano, Daisuke; Kazuto, Toyama; Tamaki, Takehiro; Fujito, Hidesato; Sezai, Akira; Okumura, Yasuo
Abstract: Aims: Congestive splenomegaly is a classic sign of organ congestion in acute decompensated heart failure (ADHF). Shear wave elastography (SWE) allows the measurement of spleen stiffness (SS). We hypothesized that SS could quantify the severity of splenic congestion and predict adverse events in ADHF. Methods and Results: This study included two cohorts: a haemodynamic cohort (62 HF patients) and an outcome cohort (115 ADHF patients). SS was measured by two‐dimensional SWE on the same day of right heart catheterization in the haemodynamic cohort. Right atrial pressure (RAP) independently correlated with SS ( β = 0.32, P = 0.002). SS was measured in the outcome cohort before discharge. The 115 patients were divided into three groups on the basis of the tertile value of SS. The third tertile SS group had a higher prevalence of severe tricuspid regurgitation, higher N‐terminal B‐type natriuretic peptide (NT pro‐BNP), and larger right ventricular diastolic diameter, than had the first tertile group and the second tertile group. During a median follow‐up period of 105 (77–135) days, adverse events occurred in 25 patients (one death and 24 rehospitalizations for HF). The third tertile SS group had a significantly higher rate of adverse events ( P < 0.001). A higher SS was independently associated with adverse events after adjusting for conventional validated risk score, liver function test, liver stiffness, and estimated RAP. Conclusions: The degree of SS at discharge can be used as a marker of residual splenic congestion, which is predictive of adverse events in patients with ADHF.